2020
DOI: 10.3390/healthcare8010021
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Still on Track”: A Qualitative Exploration of Participant Experiences of a Weight Loss Maintenance Program

Abstract: Qualitative evidence of participants’ experiences of real-life weight loss maintenance programs is important for ongoing participant engagement and can inform program improvements. The purpose of this study was to understand how participants account for their engagement with a weight loss maintenance program and the role of the program in their weight management. A qualitative study using semi-structured interviews with 17 participants of a weight loss maintenance program was conducted; common themes were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…They felt having a buddy to offer and receive support could aid in maintaining self-regulatory behaviours. The role of professional and personal support from friends and family, specifically through face-to-face contact, is consistent with other qualitative findings examining participants’ perceptions of behavioural weight loss interventions (Gorin et al, 2020; Jessen-Winge et al, 2021; McGill et al, 2020; Wing and Jeffery, 1999). Specifically, perceptions of weight loss maintenance were examined between weight loss maintainers and regainers following ⩾10% weight loss through behavioural or commercial weight loss programmes (Reyes et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…They felt having a buddy to offer and receive support could aid in maintaining self-regulatory behaviours. The role of professional and personal support from friends and family, specifically through face-to-face contact, is consistent with other qualitative findings examining participants’ perceptions of behavioural weight loss interventions (Gorin et al, 2020; Jessen-Winge et al, 2021; McGill et al, 2020; Wing and Jeffery, 1999). Specifically, perceptions of weight loss maintenance were examined between weight loss maintainers and regainers following ⩾10% weight loss through behavioural or commercial weight loss programmes (Reyes et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…The goal was to gain insights into the experience of weight management and the resulting consequences encountered. Research into the experience of substantial, sustainable weight-loss maintenance has continuously found that individuals with overweight and obesity experienced the achievement of substantial, sustainable weight-loss maintenance to be challenging due to varying factors including everyday stress [ 29 35 ], emotional eating and boredom [ 33 , 34 , 36 , 37 ], planned life events [ 14 , 29 , 30 , 38 , 39 ] as well as unplanned life events [ 29 , 33 , 34 ], amongst others. Environmental influences have also frequently been cited as potentially derailing factors including discouraging peers [ 30 32 , 39 41 ], the obesogenic food environment [ 14 , 30 ] and the inability to stay motivated without support [ 36 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Motivators generally include improved health [ 14 , 30 , 33 35 , 37 , 39 ] and self-image [ 14 , 29 , 31 , 34 , 35 , 41 , 44 , 45 ]. Studies have also highlighted the desire to decrease the experience of weight stigma as a motivator for weight-loss [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%